BONE STRESS INJURIES IN THE ARMY CADETS OF PAKISTAN MILITARY ACADEMY - Khan, Kamran; Khan, Amjad Aziz; Ahmad, Shakil; Jeilani, Asif; Khan, Zahid R. (Journal of Ayub Medical College Abbottabad, 2008)
Background: Bone stress injuries are common among army cadets during training period and these injuries give rise to morbidity and loss of training hours. Some cadets with stress fractures re-join their duties while some are kept out of services resulting in attrition and economic loss. A retrospective analysis of bone stress injuries of one hundred and twenty cadets between June 2006 and Dec 2007 was conducted from the case documents available at Institute of Nuclear Medicine, Oncology & Radiotherapy (INOR) Abbottabad. Results: The occurrence of stress fractures among cadets at Pakistan Military Academy, presenting with exercise induced pain was 68.3% amongst these cadets. Seventy fours percent f the fractures were labelled grade-I. High grade fractures were confined to tibia. Tibia was the commonest site of stress fractures in both sexes, accounting for about 73% of all stress fractures. Fifty percent of these patients were labelled as having shin splints and 3% as thigh splints. Conclusions: Most of the stress injuries were confined to the tibia. The referral was considered early as most of the stress injuries were of low grade. Keywords: Bone Stress, Stress fractures